Territorial information as strategic input for the design of human development policies at local level. A critical analysis - Pol, María Albina (Universidad del Rosario, 2011)
This article aims to analyze, from a critical perspective, the current statistic information as an input for the design of human development policies at local level. Firstly, the article reflects on two notions: the territory as an area for expansion of human capabilities and the territorial information as a strategic resource. The second part describes, from a case of study, the main weaknesses that currently present the socio-economic information available. Finally, the article concludes with some general considerations aimed to achieve progress in the development of Territorial Information Systems.